Análise geoambiental da paisagem e potencial geoturistico do município de Turvo-PR - Calegari, Elizete Besagio (2012)
This research covers the complete area of the Turvo municipality, located in the central region of the Parana state, southern Brazil. It was executed following a macro vision witch evinced its major characteristics and functions. The municipality presents a diversified landscape, with geomorphologic characteristics associated to the geological formations Serra Geral, Botucatu and Rio do Rastro, which gives it perspectives to the adventure tourism, ecotourism, geotourism and landscape tourism. The purpose of this research is to appraise the potentials of the geodiversity existent in Turvo, to the local geotourism development and, specifically, recognize, inventory and classify places of geotouristic interest, distinguish the different unities of landscape, trying to demonstrate the potentials of these places for the practice of geotourism. The diagnosis is done through the integrated analysis of the landscape, the geoconservation strategy and the matrix of strengths,weaknesses/limitations,opportunities, and threats (SWOT). The use of these methodologies combined allows recognizing the geoenviromental unities, as well as the potentials and limitations against human intervention; in addition it points the major tourism vocations of each unity. So, this research brings subsides to the realization of touristic actions, being a useful material for an efficient and ordinated territory planning.